Cohesive Devices in Student’s Writing (A Discourse Analysis on Argumentative Text) - Haqim Hasan Albana; Abdul Gafur Marzuki; Alek Alek; Didin Nuruddin Hidayat (Jurnal Pendidikan Humaniora, 2020)
Abstract: This research aims to analyse a piece of argumentative writing produced by fifth semester of Darussunnah students in a term of cohesion issues of discourse analysis. The cohesive devices are viewed as a structure of analysis to investigate the grammatical and lexical cohesion in writing. Qualitative and quantitative (mixed method) were applied in analysing the data. The quantitative analysis investigates the frequency and percentage of errors committed in student’s writing. Qualitative analysis were employed to investigate linguistic description and the explanation of the cohesion produced by student’s writing. The result showed that students have performed the cohesive devices. However, students need to improve the use of cohesive device, especially in grammatical cohesion to result higher level of cohesion.Key Words: Argumentative writing, cohesive devices, grammatical and lexical cohesion Abstrak: Penelitian ini bertujuan untuk menganalisis karya tulis argumentatif mahasiswa semester V Darussunnah dalam kerangka analisis permasalahan kohesi. Perangkat kohesif dipandang sebagai struktur analisis untuk menyelidiki kohesi gramatikal dan leksikal dalam menulis. Analisis data dilakukan secara kualitatif dan kuantitatif (metode campuran). Analisis kuantitatif penelitian ini bertujuan untuk menyelidiki frekuensi dan persentase kesalahan yang dilakukan dalam kegiatan menulis siswa. Analisis kualitatif digunakan untuk menyelidiki deskripsi linguistik dan penjelasan tentang kohesi yang dihasilkan oleh tulisan siswa. Hasil penelitian menunjukkan bahwa siswa telah melaksanakan perangkat kohesif. Namun, siswa perlu meningkatkan penggunaan perangkat kohesif, terutama pada kohesi gramatikal untuk menghasilkan tingkat kohesi yang lebih tinggi.Kata kunci:Penulisan argumentatif, perangkat kohesif, kohesi gramatikal dan leksikal